1975
DOI: 10.2466/pr0.1975.36.3.737
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Differences of Depression in Mental Hospital Admissions as Measured by the MMPI

Abstract: In 160 new hospital admissions, depression as measured by the MMPI was significantly lower in summer than in each of the other seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…(2013), all were registry studies. Six of them (Cerbus and Dallara, 1975; Christensen and Dowrick, 1983; Posternak and Zimmerman, 2002; Belleville et al ., 2013; Holloway and Evans, 2014) found no indications of seasonality, including Sato et al . (2006) that found no overall association, but higher rates of prescriptions for major depressive episode in spring among individuals with unipolar depression without depressed mixed states, and in autumn for bipolar and unipolar individuals with depressed mixed states.…”
Section: Resultsmentioning
confidence: 99%
“…(2013), all were registry studies. Six of them (Cerbus and Dallara, 1975; Christensen and Dowrick, 1983; Posternak and Zimmerman, 2002; Belleville et al ., 2013; Holloway and Evans, 2014) found no indications of seasonality, including Sato et al . (2006) that found no overall association, but higher rates of prescriptions for major depressive episode in spring among individuals with unipolar depression without depressed mixed states, and in autumn for bipolar and unipolar individuals with depressed mixed states.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the environment have also been linked to other antisocial behavioral tendencies (Friedman & Becker, 1965;Cerbus & Dallara, 1975;Banziger & Owens, 1978;Raps & Stoupel, 1992;Barker et al, 1994;Stoupel, 1999;Yan, 2000;Rotton, 2001). It has been reported that suicide increases with rises in barometric pressure and decreases in wind, drug addiction increases with greater changes in warm and cold fronts, and psychiatric admissions increase with warmer ambient temperatures.…”
Section: Weather and Human Behaviormentioning
confidence: 93%
“…Many studies examining seasonal fluctuations in depressive symptoms have used the season of hospital admission as the dependent measure (Cerbus and Dallara, 1975;Eastwood and Stiasny, 1978;Szabo and Terre Blanche, 1995;Suhail and Cochrane, 1998). Others have examined how frequency of suicide deaths fluctuates throughout the year (Zung and Green, 1974).…”
mentioning
confidence: 99%